Penggunaan Metode RGEC Untuk Menilai Tingkat Kesehatan Bank Sebelum Dan Sesudah Merger Pada PT Bank Syariah Indonesia - Ekastuti , Zaidatun; Salsabillah , Rully Salwa; Sudarsono , Sudarsono (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2024)
Bank health assessment is an assessment of various aspects that affect the performance of a bank. The assessment can determine the level of bank health that is very healthy, healthy, fairly healthy, unhealthy or even unhealthy. The purpose of this study is to determine the health level of Bank Syariah Indonesia using the RGEC method before the merger, during the merger and after the merger. The object of this study is the assessment of bank health using the RGEC method. The data used is quantitative. The data sources obtained are secondary data in the form of financial reports published by the official website https://ir.bankbsi.co.id/. The method used is the Data Collection Method and Analysis Method using the Financial Services Authority Regulation Bank Indonesia Circular Letter No. 13/24/DPNP 2011. The results of this study indicate that the assessment before the merger in 2020, the average RGEC obtained was 86% with a very healthy rating. The merger in 2021, the average RGEC obtained was 91% with a very healthy rating. After the merger in 2022 and 2023, the average RGEC obtained was 91% with a very healthy rating. Based on the results of this study, it is recommended for Bank Syariah Indonesia to continue to maintain and improve the performance that has been achieved, and to conduct periodic evaluations of the implementation of the established business strategies.